2018
DOI: 10.1155/2018/9136971
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of High-Sensitive Cardiac Troponin, Copeptin, and the Modified HEART Score for Rapid Evaluation of Chest Pain Patients

Abstract: Background Clinical short-term risk stratification is a recommended approach in patients with chest pain and possible acute myocardial infarction (AMI) to further improve high safety of biomarker-based rule-out algorithms. The study aim was to assess clinical performance of baseline concentrations of high-sensitivity cardiac troponin T (hs-TnT) and copeptin and the modified HEART score (mHS) in early presenters to the emergency department with chest pain. Methods This cohort study included patients with chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Hence, the findings from the CHOPIN trial [68] corroborate the clinical usefulness of a negative Copeptin in combination with a negative cTn but more importantly demonstrate added and independent prognostic value for prediction of outcomes within 180 days after NSTE-ACS. Additional evidence from observational trials [69][70][71][72] and a meta-analysis [73] have accumulated substantial evidence for a prognostic role of Copeptin when used together with a hs-cTn. Von Haehling [71] reported data from 2,700 patients with symptomatic coronary artery disease (CAD), who either presented with suspected ACS to the ED, or for elective coronary angiography.…”
Section: Ck-mb For Re-infarction Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the findings from the CHOPIN trial [68] corroborate the clinical usefulness of a negative Copeptin in combination with a negative cTn but more importantly demonstrate added and independent prognostic value for prediction of outcomes within 180 days after NSTE-ACS. Additional evidence from observational trials [69][70][71][72] and a meta-analysis [73] have accumulated substantial evidence for a prognostic role of Copeptin when used together with a hs-cTn. Von Haehling [71] reported data from 2,700 patients with symptomatic coronary artery disease (CAD), who either presented with suspected ACS to the ED, or for elective coronary angiography.…”
Section: Ck-mb For Re-infarction Diagnosismentioning
confidence: 99%
“…Irrespective of hs-cTn or cTn levels, patients with low levels of Copeptin had an excellent prognosis compared with patients with raised levels of both Copeptin and cTn (360-day mortality 2.8-3.6% vs 23.1-33.8%, p < 0.001). Morawiec et al [70] reported on 154 patients showing that the highest event-free survival at 30 days was achieved in patients stratified with an algorithm that combines hs-TnT, a modified HEART Score (mHS) ≤ 3, and Copeptin, with 100% (95% CI 75.3-100) NPV and 100% (95% CI 96.6-100) sensitivity. Another article by Reiter et al [75] based on patients recruited in the APACE study reported on the diagnostic and prognostic value of biomarkers added to hs-cTn.…”
Section: Ck-mb For Re-infarction Diagnosismentioning
confidence: 99%
“…However, these studies were flawed by several limitations including the lack of prospective evaluation in the observational studies with few exceptions (M€ ockel et al 2015(M€ ockel et al , Giannitsis et al 2019, small sample size and low event rates (Meune et al 2011, Bahrmann et al 2013, Sebbane et al 2013, Alqu ezar et al 2017, Morawiec et al 2018, Chenevier-Gobeaux et al 2019, false definition of dual marker testing (i.e. either component positive instead of both components negative (Meune et al 2011, Eggers et al 2012, Sebbane et al 2013, use of the previous less sensitive Copeptin assay formulation, mostly used at a cut-off of 14-17.3 pmol/L (Meune et al 2011, Eggers et al 2012, Bahrmann et al 2013, Sebbane et al 2013, Lipinski et al 2014, Raskovalova et al 2014, Morawiec et al 2018, or 12 pmol/L (Chenevier-Gobeaux et al 2019) instead of the more sensitive cut-off at the 95th percentile at 9 or 10 pmol/L (Thelin et al 2013, M€ ockel et al 2015, Alqu ezar et al 2017, Giannitsis et al 2019, Wildi et al 2019. Moreover, several studies did not exclude patients with persistent ST-segment elevations (Sebbane et al 2013, Lipinski et al 2014, Raskovalova et al 2014.…”
Section: Previous Findingsmentioning
confidence: 99%
“…However, evidence is limited since other comparative studies (Boeddinghaus et al 2017, Chapman et al 2017) and a collaborative meta-analysis (Pickering et al 2017) on the diagnostic or prognostic performance of serial or single very low hs-cTn concentrations did not evaluate the performance of DMS at all. In addition, non-exclusion of high risk patients (Mueller-Hennessen et al 2019), a wide range of troponin assay types and Copeptin cut-offs as well as statistical issues further complicate the interpretation of inconsistent study findings (Meune et al 2011, Sebbane et al 2013, Lipinski et al 2014, Raskovalova et al 2014, Alqu ezar et al 2017, Morawiec et al 2018, Chenevier-Gobeaux et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Several hs-cTnT/I based rapid algorithms have been developed in the last decade [3,18,20,28,[54][55][56][57][58]. First introduced in 2011 by the ESC guidelines for non-ST-elevation (NSTE) ACS, the ESC 0/3h algorithm was the first hs-cTnT/I based rapid algorithm that was used widely throughout the world.…”
Section: Esc 0/1h and 0/2h-algorithmsmentioning
confidence: 99%